Exploring the Trends and Spectrum of UTI-Causing Uropathogenic Bacterial Profiles and Their Antibiotic Susceptibility Patterns: A 4-Year Retrospective Study in Western Maharashtra - Bausakar, Amol; Singh, Neha; Rai, Preeti; Sharma, Pallavi; Reddy, R Mahesh (Annals of Pathology and Laboratory Medicine, 2025)
Background: Urinary tract infections (UTIs) are one of the most common and prevalent healthcare challenges worldwide, caused by uropathogens. This abstract summarizes recent research on UTI-causing uropathogens and their antibiotic susceptibility trend in a tertiary hospital over the period of four years. The study will help improve resistance surveillance and antibiotic policies, ultimately enhancing patient outcomes. Methods: A retrospective study was conducted in a tertiary care hospital for a period of 4 years (2020-2023). 21,330 urine samples of patients with UTI-like symptoms were subjected to bacterial cultures. Samples with significant bacteriuria were subjected to identification and antibacterial susceptibility testing using the VITEK® 2 COMPACT System. Result: Of 21,330 samples, 5,211 (24.43%) showed significant bacteriuria, with Escherichia coli (49.75%) being the most common uropathogen, followed by Klebsiella pneumoniae (24.69%), Pseudomonas aeruginosa (8.01%), and Enterococcus spp. (5.49%). Carbapenem-resistant K. pneumoniae isolates increased significantly from 33.21% (2020) to 59.96% (2023), while no significant rise was observed in Carbapenem-resistant E. coli and P. aeruginosa isolates. Resistance to Vancomycin (13.75%), Linezolid (9.99%), and Teicoplanin (8.12%) in Enterococcus species remained stable over four years. Resistance rates in ICU isolates were higher than those in outpatients and non-ICU inpatients. Conclusion: E. coli, K. pneumoniae, Enterococcus spp., and P. aeruginosa were the most common pathogens causing UTIs in our region. The bacterial species and antimicrobial resistance patterns seen in uropathogens varied across different patient populations that visited the tertiary care hospital. Strengthening and improving the monitoring and surveillance of bacterial resistance is very essential to minimize the spread and evolution of multi-drug-resistant organisms.